2017
DOI: 10.1002/adma.201606301
|View full text |Cite
|
Sign up to set email alerts
|

Spermatozoa as Functional Components of Robotic Microswimmers

Abstract: In recent years, the combination of synthetic micro- and nanomaterials with spermatozoa as functional components has led to the development of tubular and helical spermbots - microrobotic devices with potential applications in the biomedical and nanotechnological field. Here, the initial advances in this field are discussed and the use of spermatozoa as functional parts in microdevices elaborated. Besides the potential uses of these hybrid robotic microswimmers, the obstacles along the way are discussed, with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
126
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 140 publications
(130 citation statements)
references
References 136 publications
0
126
0
Order By: Relevance
“…Self-propelled biological structures are very intriguing due to their ability to adapt and swim in complex environments by their independent propelling systems [27]. Sperms, as a type of motile cells whose main function is the fertilization of an oocyte, are one of the most powerful natural microswimmers.…”
Section: Cells/microorganisms As Propellersmentioning
confidence: 99%
See 1 more Smart Citation
“…Self-propelled biological structures are very intriguing due to their ability to adapt and swim in complex environments by their independent propelling systems [27]. Sperms, as a type of motile cells whose main function is the fertilization of an oocyte, are one of the most powerful natural microswimmers.…”
Section: Cells/microorganisms As Propellersmentioning
confidence: 99%
“…Moreover, they can be controlled precisely using external sources such as magnetic fields, ultrasound or light [20]. For example, they have been used to isolate cells [21], perform microbiopsies [22], sense proteins [23], ligands or other molecules of interest, deliver drugs or even help sperms with motion deficiencies to reach the oocyte, all in vitro [24][25][26][27]. Nonetheless, it is worth noting that the use of these new systems entails additional difficulties, such as their control and visualization in deep tissue in real time [28].…”
mentioning
confidence: 99%
“…[22,23] These hybrid robots utilize primarily the biological propulsion of the sperm as the power source. [24] Upon completion of our work, a related study was published describing the use of sperm cells for drug delivery. [25] However, the natural intelligence of sperm cells, particularly their intrinsic chemotactic characteristics, [26] has not been explored yet.…”
Section: Doi: 101002/adbi201700160mentioning
confidence: 99%
“…The FSFSMs are not subject to the significant speed loss experienced by hybrid sperm motors guided by magnetic structures, and offer considerable advantages such as improved biocompatibility and simple fabrication process. [24,29] The concept of guiding and transporting synthetic nanoscale payloads via the intrinsic chemotactic movement of natural sperm carriers could pave the way for the development of smart and environmentally responsive micro/nanoscale vehicles that can autonomously navigate along chemical gradients.…”
Section: Doi: 101002/adbi201700160mentioning
confidence: 99%
“…Electro-optical polymer based devices are another area of study which has been taking advantage of the MPM as a powerful characterization method [9]. Moreover, recent studies showed the ability of utilizing MPM in three dimensional micro-fabricated devices including sensors, waveguides, photonic structures, and biomedical devices, using various types of light sensitive polymers [10][11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%